2002
DOI: 10.1093/jn/132.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Choline Deficiency–Induced Liver Damage Is Reversible in Pemt−/− Mice

Abstract: Hepatic tissue has two pathways for phosphatidylcholine (PC) synthesis, i.e., the cytidinediphosphocholine (CDP-choline) pathway and the methylation pathway, which utilizes phosphatidylethanolamine-N-methyltransferase (PEMT). Fatal liver damage occurs in Pemt(-/-)mice fed a choline-deficient (CD) diet. We investigated whether liver damage can be reversed by the addition of dietary choline. Mice (8 wk old) were fed the CD purified diet for 4 d, a choline-supplemented (CS) diet (CD diet + 0.4% choline chloride) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 14 publications
3
61
0
1
Order By: Relevance
“…Activities of AST and ALT in plasma, as indicators of hepatocytes damage (Waite et al 2002), were measured by spectrophotometer (Biosystems, BTS-330) and commercial kits (Sigma Chem. Co. St. Louis, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Activities of AST and ALT in plasma, as indicators of hepatocytes damage (Waite et al 2002), were measured by spectrophotometer (Biosystems, BTS-330) and commercial kits (Sigma Chem. Co. St. Louis, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Co. St. Louis, USA). Plasma corticosterone concentration, as an indicator of stress (Waite et al 2002), was measured by radioimmunoassay using tubes labeled with rabbit anti-corticosterone-antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared these values to those for the phosphatidylethanolamine methyltransferase (PEMT), which governs the alternate pathway for PtdCho synthesis in liver (52), to obtain a sense of the relative contributions of each of these proteins to PtdCho synthesis overall. We found that CCT␤2 and CCT␤3, if expressed, constitute a minor species in most tissue CCT pools, except for brain tissue.…”
mentioning
confidence: 99%
“…This enzyme uses S-adenosylmethionine as a methyl donor and forms a new choline moiety (37). When fed a diet deficient in choline, Pemt 7/7 mice developed fatty liver, severe liver damage and died; a choline supplemented diet prevented this (38) and reversed hepatic damage if begun early enough (39). The PEMT pathway is not just a minor pathway that backs up the cytidine diphosphocholine pathway for phosphatidylcholine biosynthesis.…”
Section: Dietary Intake and Endogenous Synthesis Of Cholinementioning
confidence: 99%